Effect of green waste pretreatment by sodium hydroxide and biomass fly ash on composting process - Karnchanawong S. (2017)
© 2016 Elsevier Ltd Green waste contains a major portion of lignocellulose which is hard to be decomposed. The objective of this study was to determine the effect of alkaline pretreatment using sodium hydroxide (NaOH) and biomass fly ash for the composting of Samanea saman. The experimental detail consists of seven runs, that is, control; 1%, 2%, and 3% NaOH treatments; and 6.2%, 12.4%, and 12.4% biomass fly ash treatments. The pretreatment was conducted by mixing of NaOH and fly ash with green waste for 2 d and transferring the mixture to be composted in 55-L polystyrene thermo cooler boxes. The composting was performed for 105 d. The temperature was recorded daily and the compost characteristics were analyzed every 7–14 d. The highest maximum temperature was found in the NaOH treatment. However, the mean temperatures of all the experiments were not significantly different. The initial C/N ratios of the waste for all the runs ranged from 51.11 to 54.90 before continually decreasing/increasing to be in the range of 42.64–65.28 at the end of the experiment. The high C/N ratio of the end compost in the alkaline treatment might be attributed to the high initial C/N ratio and the N loss that resulted from the high pH of the compost material. The results of the lignin mass reduction show that 1–2% NaOH and 6.2% fly ash treatments can reduce lignin 2 times better than the control. However, higher doses of alkaline matter can increase the nitrogen loss due to volatilization of ammonia in the higher pH condition. In order to enhance the decomposition of green waste and minimize the nitrogen loss in the composting process, the pretreatment by 6.2% of fly ash can be selected.